Application of computer modeling methods in the design of snow protection systems - S. A. Filimonov; K. Yu. Litvintsev; A. A. Dekterev; A. V. Minakov; V. D. Meshkova; R. A. Sharafutdinov; Yu. N. Zaharinskiy (Архитектура, строительство, транспорт)
The article discusses the use of numerical modeling methods of snow-wind flow transfer processes to determine the locations of snow protection constructions. The numerical algorithm also includes computer processing of meteorological data and a digital model of topography. Based on this approach, an analysis of the placement of snowretaining fences along a section of snow-covered road was made.